Decomposing Habitat Suitability Across the Forager to Farmer Transition. (4th July 2022) - Vernon, Kenneth B.; Yaworsky, Peter M.; Spangler, Jerry; Brewer, Simon; Codding, Brian F.
ABSTRACT: How might subsistence strategies structure the costs and benefits of habitat selection and, therefore, drive settlement patterning? We explore this question within an Ideal Distribution framework, arguing that (i) a habitat can be decomposed into its environmental covariates, (ii) their relative contributions to suitability can vary as a function of subsistence strategy, and (iii) the resulting differences will in turn lead to different population distributions across habitats. To evaluate these claims, we apply a Poisson point-process modelling approach known as maximum entropy (MaxEnt) to Archaic hunter-gatherer and Formative maize-farmer sites within the Grand Staircase-Escalante National Monument. Our results show that environmental covariates vary in their importance for each strategy and that the strategies themselves vary in their land use and habitat distribution, with Archaic foragers being widely distributed across space, Formative farmers more densely packed into areas indicative of higher maize productivity. The approach itself also has wide application to other subsistence strategies, including horticulture and pastoralism, across a range of environmental conditions.